GSTM1, GSTT1 and CYP1A1 polymorphisms and risk of oral cancer: a case-control study in Jakarta, Indonesia - Amtha, R.; Ching, C.S.; Zain, R.; Razak, I.A.; Basuki, B.; Roeslan, B.O.; Gautama, W.; Purwanto, D. (West Asia Organization for Cancer Prevention, 2009)
Genetic polymorphisms of GSTM1, GSTT1 and CYP1A1 may not be risk factors for oral cancer in the Jakarta population.